2007
DOI: 10.1111/j.1365-2265.2007.02971.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic consequences of variation across the aldosterone synthase and 11‐beta hydroxylase locus in a hypertensive cohort: data from the MRC BRIGHT Study

Abstract: Hypertensives homozygous for the -344 T allele of CYP11B2 demonstrate altered 11beta-hydroxylase efficiency (CYP11B1); this is consistent with the hypothesis of a genetically determined increase in adrenal ACTH drive in these subjects. The correlation between excretion of aldosterone and cortisol metabolites and suggests that, in TT subjects, ACTH exerts an important common regulatory influence on adrenal corticosteroid production in subjects with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…These are subtle but significant differences in mRNA levels, which provide a simple putative mechanism to explain the association, reported elsewhere, of Haplotype2 polymorphisms with lower aldosterone levels 7,24 and greater 11β-hydroxylation efficiency. 25,26 These findings are also consistent with the known association between SNPs in the 5′ regulatory region of CYP11B1 and minor impairment of 11β-hydroxylation efficiency 14 ; the relevance of this to the long-term risk of hypertension has been the subject of a detailed review elsewhere. 27 We do not have data on circulating corticosteroid levels in the cohorts studied, and the links among genotype, intermediate biochemical phenotype, and BP still need to be clarified.…”
Section: Discussionsupporting
confidence: 73%
“…These are subtle but significant differences in mRNA levels, which provide a simple putative mechanism to explain the association, reported elsewhere, of Haplotype2 polymorphisms with lower aldosterone levels 7,24 and greater 11β-hydroxylation efficiency. 25,26 These findings are also consistent with the known association between SNPs in the 5′ regulatory region of CYP11B1 and minor impairment of 11β-hydroxylation efficiency 14 ; the relevance of this to the long-term risk of hypertension has been the subject of a detailed review elsewhere. 27 We do not have data on circulating corticosteroid levels in the cohorts studied, and the links among genotype, intermediate biochemical phenotype, and BP still need to be clarified.…”
Section: Discussionsupporting
confidence: 73%
“…32 Second, in normal subjects, there is a recognized diurnal variation in aldosterone that mirrors that of cortisol, consistent with an effect of ACTH on synthesis of the mineralocorticoid. 33 We have also shown positive correlations between aldosterone and glucocorticoids (and androgens) in a large population-based study, which we suggest is a consequence of shared regulation, 34 and have shown that this might be related to genetic variation at the CYP11B1/B2 locus. 9 Finally, aldosterone regulation is typically maintained as a result of input from multiple trophins, and we proposed previously that the effect of ACTH is to modulate the aldosterone responsiveness to other factors such as angiotensin II and potassium.…”
Section: Discussionmentioning
confidence: 93%
“…They were recruited from the local population as part of the control group for the MRC Bright study. 5 Approval for the study was granted by the local Ethics Committees and fully informed written consent from all of the participants was obtained. Anonymized routine patients' samples (n ¼ 266) were used in the ARR method comparison and were from hypertensive patients suspected of suffering from primary or secondary aldosteronism.…”
Section: Patientsmentioning
confidence: 99%